An Acoustic Characterization of Prosodic Differences in Autism Spectrum Disorder and First-Degree Relatives - Patel, Shivani P. (J Autism Dev Disord, 2020)
This study examined prosody through characterization of acoustic properties of the speech of individuals with ASD and their parents, during narration. A subset of utterances were low-pass filtered and rated for differences in intonation, speech rate, and rhythm. Listener ratings were minimally related to acoustic measures, underscoring the complexity of atypical prosody in ASD. Acoustic analyses revealed greater utterance-final fundamental frequency excursion size and slower speech rate in the ASD group. Slower speech rate was also evident in the ASD parent group, particularly parents with the broad autism phenotype. Overlapping prosodic differences in ASD and ASD Parent groups suggest that prosodic differences may constitute an important phenotype contributing to ASD features and index genetic liability to ASD among first-degree relatives.